Designing fashion [videorecording]. (VEA, 2011)
"This program investigates the steps taken by fashion designers to develop their ideas into end products, from that initial spark of inspiration to final production. Throughout the program viewers see how fashion designers use various tools, equipment and drawing techniques to visually display their inspirations and ideas, how they use of computer aided design (CAD) to enhance and support their work, and finally, the steps involved in sampling, pattern making and production. The program is further enhanced by insightful interviews with top fashion designers including legendary Australian fashion designer, Akira Isogawa, Vanessa Rochman, head designer at Metallicus, and textiles designer Kaffe Fassett"-- Container.